Social media influencers and e-WOM on Skintific products purchase intentions: the mediating role of brand image - Zulaika Uma Hafizah; Kussudyarsana Kussudyarsana (Jurnal Mantik, 2024)
Social media is a digital marketing tool that is more adaptive and provides convenience for its users, including product campaign. Changes in consumer behavior have made companies consider new value propositions for consumers, including utilizing social media influencers and the presence of e-WOM to increase potential consumer’s purchasing intentions. This research aims to identify the influence of social media influencers and e-WOM on Skintific products purchase intention through brand image. The research used a quantitative approach with a correlational research type. The sampling technique used was nonprobability sampling, specifically purposive sampling. Data was obtained from Solo Raya respondents. The sample in this study amounted to 200 respondents. The data analysis technique used in this research was SEM PLS (Structural Equation Modeling - Partial Least Square) using SmartPLS statistical software. Results indicate a positive effect between social media influencers and e-WOM on consumer’s purchase intention with brand image mediating this relationship